WBAN System Organization, Network Performance and Access Control: A Review - Al-Barazanchi I.; Razali R.A.; Hashim W.; Alkahtani A.A.; Abdulshaheed H.R.; Shawkat S.A.; Jaaz Z.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Access control; Data communication systems; Data transfer; Electrocardiography; Medical computing; Network performance; Sensor nodes; Body networks; Central control; Central control unit; Control unit; High costs; Network access; Organization networks; Patients' conditions; Systems organization; Wireless sensor; Wireless local area networks (WLAN)